385 The upper limb rotation test: reliability and validity study of a new upper extremity physical performance test. (3rd March 2020) - Decleve, Philippe; Attar, Trystan; Benameur, Tasnim; Gaspar, Valentine; Cant, Joachim Van; Cools, Ann
Abstract : Background: Screening tests must be reliable, sensitive, specific, inexpensive, easy to perform and widely available. Physical performance tests (PPTs) meet these criteria and are routinely used for injury prediction, performance enhancement or post-rehabilitation outcome measures. Objectives: The primary purpose was to evaluate the reliability of the Upper Limb Rotation Test (ULRT). The secondary objective was to evaluate the relationship between the ULRT and two PPTs (Seated Medicine Ball Throw-SMBT and Closed Kinetic Chain Upper Extremity Stability Test - CKCUEST), trunk rotation range of motion (SRT) and shoulder rotational isometric strength using the Self-Assessment Corner (SAC). Design: A two session measurement design was used. Setting: Laboratory setting. Patients (or Participants): A sample of 91 healthy adults participated to establish the reliability and validity of the ULRT. Interventions (or assessment of risk factors): We used a two-session measurement design separated by seven days to evaluate the reliability. We used the SMBT, CKCUEST, SAC and the SRT to determine relationships with the ULRT. Main outcome measurements: Relative reliability was determined by intraclass correlation coefficients (ICC). Absolute reliability was quantified by standard error of measurements and minimal detectable change (MDC). Correlation analysis was determined by the Pearson correlation coefficient (r). Results: Results showed good reliability ranging from 0.76 (Dominant Arm- DA) to 0.78 (Non Dominant Arm- NDA). The SEM95 varied from 1.14 touches (DA) to 1.18 touches (NDA). The MDC95 ranged from 3.15 touches (NDA) to 3.27 touches (DA). A moderate correlation was found between the ULRT and CKCUEST scores (r range=0.505–0.553 for DA; r range=0.566–0.615 for NDA). A moderate correlation was found between ULRT (NDA) and SMBT scores (r range=0.544–0.556). Conclusions: Results demonstrated good relative reliability and clinically acceptable absolute reliability values for the ULRT. Results showed that performances on the ULRT were moderately correlated with the CKCUEST and the SMBT (NDA).